2004
DOI: 10.1089/154585404774101653
|View full text |Cite
|
Sign up to set email alerts
|

Maternalalk8Promoter Fragment Directs Expression in Early Oocytes

Abstract: Zebrafish Alk8 is a novel type I TGFbeta family member receptor that functions in Bmp signaling pathways to direct dorsoventral patterning of the early embryo. Both alk8 mRNA and protein is expressed in a variety of tissues, including teeth, eye, heart, blood, notochord, muscle, neural tissues, and neural crest cells (NCC's). Previous functional analyses, performed by microinjection of constitutively active (CA) and dominant negative (DN) alk8 mRNAs, revealed early developmental requirements for alk8. The alk8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Maternal products are produced during oogenesis and stored in the mature oocyte and can initiate developmental cascades that carry out the embryonic developmental program (Pelegri, 2003). The roles of maternal factors in zebrafish, such as alk8 (Payne-Ferreira et al, 2004), tcf-3 (Kim et al, 2000), smoothened (Varga et al, 2001) and one eyed pinhead (Gritsman et al, 1999) have been reported. Here, for the first time, we demonstrate that an upstream 2.9-kb segment of the k18 gene is capable of driving k18 expression before mid-blastula transition and is sufficient to recapitulate the endogenous k18 transcription.…”
Section: Zebrafish K18 Transcripts Are Maternally Inheritedmentioning
confidence: 99%
“…Maternal products are produced during oogenesis and stored in the mature oocyte and can initiate developmental cascades that carry out the embryonic developmental program (Pelegri, 2003). The roles of maternal factors in zebrafish, such as alk8 (Payne-Ferreira et al, 2004), tcf-3 (Kim et al, 2000), smoothened (Varga et al, 2001) and one eyed pinhead (Gritsman et al, 1999) have been reported. Here, for the first time, we demonstrate that an upstream 2.9-kb segment of the k18 gene is capable of driving k18 expression before mid-blastula transition and is sufficient to recapitulate the endogenous k18 transcription.…”
Section: Zebrafish K18 Transcripts Are Maternally Inheritedmentioning
confidence: 99%
“…For undifferentiated germ cells, the askops ( kop ) promoter has been used to label the migrating PGCs until 3 dpf (Blaser et al 2005 ), the Tg ( ddx4 : ddx4-EGFP ) zf45Tg (previous name: Tg ( vasa:EGFP )) can be used to label PGCs from 1 dpf (Krovel and Olsen 2002 ), the piwil1 promoter in Tg ( piwil1 : EGFP ) uc1Tg (previous name: Tg ( ziwi : EGFP )) can specifically drive EGFP expression in the undifferentiated germ cells after 7 dpf (Leu and Draper 2010 ), and by using a Gal4/UAS system and the kop promoter, our previous study has shown that the undifferentiated germ cells could be visible from the shield stage to 25 dpf (Xiong et al 2013 ). For female germ cells, the Tg ( -0.5zp3b : GFP ) m1032Tg (previous name: Tg ( zpc0.5 : EGFP )) labels all stages of oocytes (Onichtchouk et al 2003 ), the vasa promotor can be used to label the early stages of oocyte but not oogonia (pre-meiotic germ cells) (Krovel and Olsen 2004 ; Leu and Draper 2010 ; Wang et al 2007 ), and Tg ( piwil1 : EGFP ) uc1Tg could specifically label the oogonia and oocytes (Leu and Draper 2010 ), whereas the Tg ( alk8 : EGFP ) only labels the early chromatin nucleolus-stage oocytes (stage IA oocytes) (Payne-Ferreira et al 2004 ). For male germ cells, both Tg ( ddx4 : ddx4-EGFP ) zf45Tg and Tg ( piwil1 : EGFP ) uc1Tg label the spermatogonia and spermatocytes (Leu and Draper 2010 ).…”
Section: Introductionmentioning
confidence: 99%